(untitled) (Neo Scientific Peer Reviewed Journal, 2025)
The article analyzes the scientific-theoretical foundations of speech etiquette, its practical aspect, and the quality of its relevance to ethical standards in language communication. The study of language not only in relation to communication, but also in its integral connection with ethics, education and upbringing, and the issues of interrelationship between its linguistic and cultural aspects have been studied.